Toxicological evaluation of Diakure, an antidiabetic polyherbal formulation - Shawn Tomy; Ujwala TK; Sandra Celine; C Senthil Kumar; Sam Johnson Udaya Chander J (International Journal of Phytomedicine, 2016)
Context and Purpose of the Study: DiaKure is a hypoglycemic polyherbal formulation prepared indigenously based on knowledge of traditional medical practitioners, which contains polyherbal mixture of Vetiveria zizanioides (root), Hemidesmus indicus (rhizome), Strychnos potatorum (seed), Salacia reticulata (bark), Holarhena antidysenterica (seed), Cassia auriculata (bark), Trigonella graecum (seed) and Acacia catechu (bark) and each individual herb has scientific background in treating diabetes by the folk medical practitioners in various communities of India. The main aim of present study is to conduct an acute and sub-acute toxicological evaluation on DiaKure (an anti-diabetic polyherbal formulation), which was indigenously developed. The powder formulation is made into a decoction for better effect and easy administration. Materials and Methods: In acute toxicity tests, four groups of Wistar rats were orally treated with doses of 5, 50, 300 and 2000 mg/kg/day of DiaKure, and general behaviour, adverse effects, and mortality were recorded for up to 14 days. In sub-acute toxicity study, rats received DiaKure at the doses of 200, 500, and 1000 mg/kg/day for 28 days, and biochemical, hematological, and histopathological changes in tissues (liver, kidney, heart, and brain) were determined. Main Findings: DiaKure did not produce any signs of toxicity or mortality in the acute toxicity test. Sub-acute toxicity study with DiaKure also did not show any change in food or water consumption, hematological, or biochemical profiles. Minimal rise in body weight was noted in group III rats. Further histological study shows no necrosis or infiltration. 1000 mg/kg-treated animal showed microvesicular steatosis in individual hepatocytes. Implications: The above data showed that DiaKure could be safe for clinical use at a dose level less than or equal to 500 mg/kg. This toxicological evaluation gives this polyherbal mixture a scientific validation to the ancestral knowledge of various communities in India.